2018
DOI: 10.1021/acs.jpca.7b10958
|View full text |Cite
|
Sign up to set email alerts
|

The X40×10 Halogen Bonding Benchmark Revisited: Surprising Importance of (n–1)d Subvalence Correlation

Abstract: We have re-evaluated the X40×10 benchmark for halogen bonding using conventional and explicitly correlated coupled cluster methods. For the aromatic dimers at small separation, improved CCSD(T)-MP2 "high-level corrections" (HLCs) cause substantial reductions in the dissociation energy. For the bromine and iodine species, (n-1)d subvalence correlation increases dissociation energies and turns out to be more important for noncovalent interactions than is generally realized; (n-1)sp subvalence correlation is much… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 102 publications
(245 reference statements)
5
56
0
Order By: Relevance
“…As seen in Table 1, about 0.1 kcal/mol can be gained in WTMAD2: in-depth analysis (Table ESI- 14) reveals that this improvement is primarily confined to the subsets BSR36 (bond separation reactions), HAL59 (halogen bonding), and HEAVY28 (heavy p-block compounds). The importance of subvalence correlation for halogen-bonded species has been shown previously 63 for the X40x10 dataset. 60 The popular simple hybrids B3LYP-D3BJ and PBE0-D3BJ are nearly tied at WTMAD2=6.5 kcal/mol.…”
Section: Dsd Double Hybrids and Refitssupporting
confidence: 61%
“…As seen in Table 1, about 0.1 kcal/mol can be gained in WTMAD2: in-depth analysis (Table ESI- 14) reveals that this improvement is primarily confined to the subsets BSR36 (bond separation reactions), HAL59 (halogen bonding), and HEAVY28 (heavy p-block compounds). The importance of subvalence correlation for halogen-bonded species has been shown previously 63 for the X40x10 dataset. 60 The popular simple hybrids B3LYP-D3BJ and PBE0-D3BJ are nearly tied at WTMAD2=6.5 kcal/mol.…”
Section: Dsd Double Hybrids and Refitssupporting
confidence: 61%
“…Unfortunately, it is expensive and not practical for normal application studies. Thus, it is mainly used for benchmarking purposes for small halogen-bonded systems [36][37][38][39]. Density functional theory (DFT) methods are popular alternatives because they provide sufficient accuracy with significantly lower computational expense.…”
Section: Computational Methods For Xb Organocatalysismentioning
confidence: 99%
“…Based on an extensive comparison of wave function and DFT methods on geometries and dissociation energies of halogen-bonded systems, Kozuch and Martin concluded that functionals with high exact exchange or long-range corrections, e.g., M06-2X [40], ωB97XD [41], and double hybrids, are suitable [36]. As the M06-2X functional and other latest versions of Minnesota functionals, e.g., MN15 [42], are well parametrized for noncovalent interactions and kinetics [36][37][38], M06-2X is a popular choice for studying XB organocatalysis [43]. For liquid-phase studies, the SMD universal solvation model [44] is a popular method to study the implicit solvation effect.…”
Section: Computational Methods For Xb Organocatalysismentioning
confidence: 99%
“…In this context, electronic structure methods constitute a precious (and almost exclusive) source of information on biochemically-relevant noncovalent interactions between individual molecules -which, in turn, often used for the parametrization and calibration of more approximate computational modeling techniques (such as classical molecular mechanics force fields). [7][8][9][10][11] Having been involved in a few recent quantum chemical investigations of noncovalent complexes, [12][13][14][15][16] we shall now attempt to employ B3LYP/TZVP calculationswhich have been shown to be capable of providing reliable noncovalent interaction energetics 17 -for the purpose of calculating energy differences associated with the aforementioned substitutions. In such manner, reliable energetic "gains/losses" which result from these particular substitutions may be quantitatively assessed, so that important practical conclusions regarding the above prediction may be drawn.…”
Section: Introductionmentioning
confidence: 99%